2012
DOI: 10.3389/fcimb.2012.00164
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive intratracheal inoculation method for the study of pulmonary melioidosis

Abstract: Pulmonary melioidosis, a disease manifestation caused by the bacterium Burkholderia pseudomallei, has been studied using aerosols or intranasal (IN) inoculation in small animal models. Both have inherent disadvantages which may not accurately model primary pulmonary melioidosis in humans. Intratracheal inoculation (IT) by direct visualization of the tracheal opening offers an alternative technique for infection that overcomes the disadvantages of aerosol and IN challenge. In this study, we describe a method wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Both our laboratory and others have previously shown that the nasal cavity represents the predominant site of B. pseudomallei colonization in intranasally inoculated mice [73,93], whereas direct lung instillation of bacteria can abrogate nasal cavity colonization and the associated central nervous system involvement [78,99]. We have further characterized that lung-specific instillation of B.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Both our laboratory and others have previously shown that the nasal cavity represents the predominant site of B. pseudomallei colonization in intranasally inoculated mice [73,93], whereas direct lung instillation of bacteria can abrogate nasal cavity colonization and the associated central nervous system involvement [78,99]. We have further characterized that lung-specific instillation of B.…”
Section: Introductionmentioning
confidence: 67%
“…The over-representation of these symptoms in mice have led us, and others, to investigate alternatives to the standard approaches of inoculating mice with B. pseudomallei through the nares. A recently developed intratracheal model of respiratory melioidosis succeeded in abrogating CNS infections, suggesting that URT colonization is directly responsible for the high levels of meningitis reported in the murine model [99,105]. Our current studies focused on advancing these findings by identifying whether URT infection in the mouse impacts the overall course of disease and ask whether these impacts might influence both basic and translational studies of respiratory melioidosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations